PENGARUH BACAAN MUROTTAL ALQURAN YANG DIPERDENGARKAN PADA PASIEN STROKE ISKEMIK AKUT TERHADAP LUARAN KLINIS - Susi Ifati,* Dodik Tugasworo,* Dwi Pudjonarko* (Neurona Majalah Kedokteran Neuro Sains, 2019)
INTRODUCTION QURAN RECITATION HAS A HIGH SPIRITUAL AND RELIGIOUS VALUE AND EFFECT TO ISLAM BELIEVER AND ALSO HAS BEAUTIFUL AND REGULAR TONE SO THAT IT IS BELIEVED TO BE USEFUL TO CURE VARIOUS DISEASES DEPRESSION AND ANXIETY ARE COMMON AND ADD TO WORSENING OUTCOMES OF STROKE THERE WAS SPIRITUAL CORRELATION BETWEEN DECREASED EMOTIONAL DISTRESS AND DEPRESSION ASSOCIATED WITH POOR OUTCOME OF STROKE QURAN RECITATION COULD BE USED AS SPIRITUAL RELAXATION TECHNIQUE THUS IMPROVE THE EFFECT OF MENTAL HEALTH